Oxidation effects on CuInxGa1-xSeyS2-y thin film growth by solution processes - Park, Se Jin; Lee, Eunjoo; Jeon, Hyo Sang; Gwak, Jihye; Oh, Min-Kyu; Min, Byoung Koun (ELSEVIER SCIENCE SA, 2012)
The oxidation effects on CuInxGa1-xSeyS2-y (CIGS) thin film growth by precursor solution based coating method with a three-step heat treatment process (oxidation, sulfurization, and selenization) were investigated to optimize the oxidation conditions for realizing highly efficient thin film solar cells. Oxidation by air-annealing at elevated temperature after coating with Cu, In, and Ga precursor solution on Mo-coated soda-lime glasses removed residual carbon impurities, resulting in nearly carbon-free CIGS film. However, the air-annealing at above 400 degrees C induced undesirable oxidation of a Mo layer coated on a soda-lime glass substrate, which deteriorated solar cell performance, particularly open circuit voltage. The optimum air-annealing temperature resulting in minimal carbon impurities, as well as Mo oxidation, was found to be around 350 degrees C, and the CIGS film synthesized with this optimum oxidation condition exhibited similar to 4% solar cell efficiency at standard irradiation conditions. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: LOW-COST; SOLAR-CELLS; NONVACUUM; INK